Evaluation of Flexibility and Thickness of Cleft Lip Scars After Treatment with Microneedling Technique: a Cohort Trial - Mohamad Alghazawy; Yasser Almodalal (Mattioli1885, 2023)
Introduction:The early surgical treatment of the cleft lip led to a postoperative scar formation which may affect the physiological and psychological aspects of the patient. Objectives: Evaluating the improvement rate of thescar flexibility and thickness of the cleft lip scar after treatment with the microneedling. Methods: Sixteen patients (12 females and 4 males), aged 16-30 years who had a cleft lip scare were included in the current study.All patients suffered from a visible defective scar in the upper cleft lip.All patients were treated with a microneedling pen device combined with topical application of oil-based hyaluronic acid.The procedure was performed in 4 sessions with 3-week intervals between sessions.The scars were assessed by the patient and an external observer using the Patient and Observer Scar Assessment Scale. Results:Thickness of the scar was improved according to the patient and observer opinions (67.28% and 61.55% respectively). Flexibility was improved according to the patient observer opinion (65.57% and 60.25% respectively). Conclusions: Microneedling treatment can be considered as an effective method for the treatment of the defective scars resulting from the cleft lip plastic surgery.The microneedling technique is a simple,easy, safe, non-invasive, and low-cost procedure.